The relationship between information technology usage and job satisfaction in administration at Universiti Tun Hussein Onn Malaysia - Younis Al-Ashqar, Sayf Mohamed Dhiya (2013)
The issue of job satisfaction has been in discussion for long time around the world. Nowadays, researchers are more interested to study about job satisfaction due to global development in various fields, especially those related to information technology (IT) areas. Paradoxically, many IT research reports claim that investment in IT does not directly contribute to higher organizational performance, such as productivity. It is generally acceptable, the fact that high job satisfaction at workplace contributes to higher performance quality. As such, this research seeks to study relationship between IT usage and job satisfaction, focusing on people who are always attached to IT facilities in their work. The findings of this study are important as many organizations now work around IT infrastructure, especially university administrators. Normally, if the job satisfaction is high, then performance quality of the organization will be high and vice-versa. Therefore, it is crucial to investigate the antecedent of what makes job satisfaction high, such as IT and its supporting attributes. In this study, it focuses on the relationship between the three sections in the structure of the study, namely independent variable (demography), first dependent variable (IT usage in administration) and second dependent variable (job satisfaction). The quantitative method is applied to collect all data for this study which is known as survey approach. Questionnaires are finalized and sent to UTHM administrators and 277 sample respondents are gathered. Survey data are analyzed through statistical method of analysis using SPSS. Three domains of IT usage in Administration, namely Training, Strategy and Data Quality, are compared with 6 demographic elements. T-test, One-way ANOVA and the Least Significant Difference (LSD) test are applied to identify the level of three IT usage in Administration domains and their significant differences. Methodological tool of Pearson correlation is used to analyze relational the relationship between IT usage and job satisfaction. This study found that the relationship between IT usage and job satisfaction, among university administrators, is positive and highly correlated.